2020
DOI: 10.1016/j.bpj.2019.11.349
|View full text |Cite
|
Sign up to set email alerts
|

The Inner Junction Complex of the Cilia is an Interaction Hub that Involves Tubulin Post-translational Modifications

Abstract: ABD) preferentially engages actin in the presence of mechanical load across actin filaments (''mechanoaccumulation''), while vinculin's ABD does not. Simultaneous optical trapping and confocal microscopy experiments demonstrate that a load of 1pN across actin activates a-catenin ABD binding. Atomic-resolution cryo-EM structures of the metavinculin ABD-actin (2.9Å ) and a-catenin ABD-actin (3.2Å ) complexes demonstrate both ABDs undergo major conformational changes upon actin engagement, prominently at their N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(69 citation statements)
references
References 0 publications
3
66
0
Order By: Relevance
“…Interestingly, the N-terminal portion of RIB72 follows a 16 nm periodicity and interacts with other 16 nm repeats MIPs including FAP106, FAP126 and FAP52, which constitute a direct link between PFs of the A- and B-tubules ( Figure 2a and 2b ). FAP52 makes extensive contacts to FAP276 that also follows 16 nm periodicity [ 66 ] ( Figure 2a ). Both FAP52 and FAP276 display an overall Y–shape and connect perpendicularly on the MTDs with the inner junction formed by the PACRG/FAP20 complex, the groove between microtubules B09 - B10 and FAP106 ( Figure 2a , [ 35 , 66 ]).…”
Section: Molecular Structure Of Ciliary Doublet Microtubules and Assomentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the N-terminal portion of RIB72 follows a 16 nm periodicity and interacts with other 16 nm repeats MIPs including FAP106, FAP126 and FAP52, which constitute a direct link between PFs of the A- and B-tubules ( Figure 2a and 2b ). FAP52 makes extensive contacts to FAP276 that also follows 16 nm periodicity [ 66 ] ( Figure 2a ). Both FAP52 and FAP276 display an overall Y–shape and connect perpendicularly on the MTDs with the inner junction formed by the PACRG/FAP20 complex, the groove between microtubules B09 - B10 and FAP106 ( Figure 2a , [ 35 , 66 ]).…”
Section: Molecular Structure Of Ciliary Doublet Microtubules and Assomentioning
confidence: 99%
“…FAP52 makes extensive contacts to FAP276 that also follows 16 nm periodicity [ 66 ] ( Figure 2a ). Both FAP52 and FAP276 display an overall Y–shape and connect perpendicularly on the MTDs with the inner junction formed by the PACRG/FAP20 complex, the groove between microtubules B09 - B10 and FAP106 ( Figure 2a , [ 35 , 66 ]). Furthermore, both the N- and C-terminus of FAP276 contact the tubulin lattice [ 66 ], which may provide additional stability in gluing the A- and B-tubules together at the inner junction.…”
Section: Molecular Structure Of Ciliary Doublet Microtubules and Assomentioning
confidence: 99%
See 1 more Smart Citation
“…These densities have been termed Microtubule Inner Proteins, or MIPs. Several recent studies have identified the proteins and potential functions of some MIPs in ciliates and flagellates (Ichikawa et al, 2017;Khalifa et al, 2020;Kirima and Oiwa, 2018;Ma et al, 2019;Owa et al, 2019;Stoddard et al, 2018;Urbanska et al, 2018). High-resolution structures, especially in Chlamydomonas reinhardtii doublet microtubules, provide a strong basis for identification and characterization of these proteins (Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, in this review, we use human subunit names, except for the IFT proteins, where we use the well-established Chlamydomonas reinhardtii nomenclature (even when discussing orthologues in other species) [ 17 , 18 ]. Exciting progress has also been made in understanding the structures of the cargo-binding BBSome complex and the microtubule doublet, for which the reader is referred to recent articles [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%